How Important is e-WOM for an Agrotourism in Batu City? Second-order PLS-SEM Approach - Nurirrozak, Muhamad Zahran; Maulidah, Silvana; Haryati, Novi; Isaskar, Riyanti (Universitas Mercu Buana, 2024)
Objectives: The objective of this research is to compare the influence of each dimension (first-order e-WOM) with its second-order e-WOM. This research also examined how e-WOM can influence tourists' decision behavior and satisfaction in Batu City agrotourism. Methodology: This research was conducted using primary data in 2023. The population in this study consists of 119 respondents who have visited agrotourism in Batu City and obtained information about agrotourism from e-WOM on Social Networking Services. The data was processed using Warp-Partial Least Square (WarpPLS) 8.0.Finding: E-WOM has proven itself as a valuable source of information for tourists visiting agrotourism in the city of Batu. With the help of e-WOM, tourists can obtain more up-to-date insights into the conditions of agrotourism. Agrotourism operators also benefit since they receive free marketing from their tourists.Conclusion: Overall, this research results indicate a contrasting comparison between the first-order e-WOM model and the second-order e-WOM. Only two dimensions of e-WOM, namely the valence of opinion and content, have a direct influence on visitation decisions and tourist satisfaction. Additionally, this study demonstrates that all three dimensions of e-WOM collectively have a significant impact on tourist behavior. Second-order e-WOM has a more substantial impact on tourists in influencing their decisions and satisfaction levels.